Perception of Hong Kong Teenagers and Young Adults on Esports Participation: A Qualitative Study Using Theory of Planned Behavior - Wong, Ming Yu Claudia; Chung, Pak-Kwong; Ou, Kailing; Leung, Ka-Man (Frontiers in Psychology, 2021)
Esports is a rapidly growing industry worldwide, and it is making significant inroads in Hong Kong as well. However, owing to debates regarding the distinction between Esports and video gaming and the potential negative effects of engaging in Esports, its development in Hong Kong is still immature. Therefore, this qualitative study investigated the perceptions and attitudes of teenagers and young adults toward Esports development and engagement, using the theory of planned behavior. Twenty-five teenagers and young adults (male = 24, female =1) participated in this study, with their ages ranging from 15 to 29 years. Our results revealed the views of Hong Kong teenagers and young adults on the beneficial and deleterious outcomes (goal setting and achievement, physical health, socialization and teamwork, psychological benefits, academics and time distribution, physical strain, negative social image, and perception toward sport participation), subjective norms (parents, peers, teachers, and modeling effect), and barriers and facilitators (balance between academics and Esports, capability, career prospects and future reality, psychological benefits, and peer encouragement and support) of participating in Esports. Additionally, the results of this qualitative study may contribute toward a deeper understanding of Hong Kong Esports players to develop a theory of planned behavior construct for capturing the beliefs and perceptions of Hong Kong teenagers toward Esports.